Relationships Between Stress Management and Perimenstrual Symptoms among Young Japanese Working Women - Fukuyama, Misa; Watanabe, Hiroko (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2025)
Background: Perimenstrual symptoms can decrease the productivity of working women and interfere with their daily lives. Women with lower stress management skills are less flexible in choosing stress-coping strategies, cannot manage stress appropriately, and may experience severe perimenstrual symptoms. Purpose: This study aimed to determine the relationship between stress management skills and perimenstrual symptoms among young Japanese working women. Methods: The participants were Japanese working women aged 20–29 years who were not on leave of absence from work, regardless of their profession or employment status. Stress management skills were assessed using the Sense of Coherence [SOC-13] and Brief Scale for Coping Profile [BSCP]. Perimenstrual symptoms assessed using the Menstrual Distress Questionnaire [MDQ]. Results: Of the participants with symptoms, 158 (89.3%) experienced some disruption. Premenstrual MDQ scores were negatively associated with adaptive qualities for coping with stress and positively associated with stress coping by changing one’s point of view. MDQ scores during menstruation were negatively associated with adaptive qualities for coping with stress and stress coping through avoidance and suppression. Conclusion: Perimenstrual symptoms were more severe among the participants with inadequate stress management.